2020
DOI: 10.2139/ssrn.3642977
|View full text |Cite
|
Sign up to set email alerts
|

The Income and Consumption Effects of Covid-19 and the Role of Public Policy

Abstract: We provide empirical evidence on the labour market impacts of covid-19 in the UK and assess the effectiveness of mitigation policies. We estimate the relationship between employment outcomes and occupational and industrial characteristics and assess the effects on consumption. 70 percent of households in the bottom fifth of the income distribution must cut consumption within one week. Finally, we compare the effectiveness the UK's Coronavirus Job Retention Scheme to Economic Impact Payments in the US. The EIPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…One early study used differential telework ability and essential worker distribution to identify negative labor shocks by occupation, 31 while another examined the same outcome using physical proximity predictors from O*NET 32 . Other studies have used O*NET data to create indices reflecting the ease of remote work, and concluded that the economic burden of COVID‐19 falls disproportionately on low income workers, 33,34 women, and workers with low educational attainment 35 . These economic outcomes represent variable social determinants of health that are crucial in understanding the differential impact of COVID‐19 on individuals and populations 36 and may lend support to social insurance as a means to reduce hardship in particularly vulnerable workers 37 …”
Section: Discussionmentioning
confidence: 99%
“…One early study used differential telework ability and essential worker distribution to identify negative labor shocks by occupation, 31 while another examined the same outcome using physical proximity predictors from O*NET 32 . Other studies have used O*NET data to create indices reflecting the ease of remote work, and concluded that the economic burden of COVID‐19 falls disproportionately on low income workers, 33,34 women, and workers with low educational attainment 35 . These economic outcomes represent variable social determinants of health that are crucial in understanding the differential impact of COVID‐19 on individuals and populations 36 and may lend support to social insurance as a means to reduce hardship in particularly vulnerable workers 37 …”
Section: Discussionmentioning
confidence: 99%
“…Dynarski and Sheffrin (1987) and Stephens (2001) argue that blue collar workers have shorter unemployment spells and their consumption is less sensitive to a change in employment status. Similarly, other factors such as age, gender and educational level are being linked to differing individual consumption behaviours during the pandemic (Minguez et al 2020 andPiyapromdee andSpittal (2020)). In Sect.…”
Section: Related Literaturementioning
confidence: 99%
“…Of significance, the economic impact of the COVID‐19 pandemic has had a disproportionately negative impact on workers who have traditionally experienced vulnerability (e.g., certain racialized communities, low‐wage workers, and immigrants) 210‐216 . For instance, data from Canada highlighted that in some regions over two‐thirds of COVID‐19 infections have been experienced by racialized groups 212 .…”
Section: Resultsmentioning
confidence: 99%